2011
DOI: 10.1080/01635581.2011.589958
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Affect Lung Cancer Risk in Never Smokers

Abstract: A number of studies suggest a role of dietary factors as risk predictors of lung cancer in never smokers. However, it is difficult to interpret the observed associations of lung cancer risk with any particular dietary item due to high correlation among different dietary items. In this study, we derived uncorrelated patterns of dietary items in the never smokers and evaluated the association of these patterns with lung cancer risk, using food frequency data from 299 never-smoker lung cancer patients and 317 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…This observation was consistent with the findings from previous dietary pattern studies on lung cancer that the beneficial effects of dietary patterns characterized by high consumption of fruits or vegetables were only evident in current or former smokers456910. Smoking causes lung cancer in part through its pro-oxidant properties31.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation was consistent with the findings from previous dietary pattern studies on lung cancer that the beneficial effects of dietary patterns characterized by high consumption of fruits or vegetables were only evident in current or former smokers456910. Smoking causes lung cancer in part through its pro-oxidant properties31.…”
Section: Discussionsupporting
confidence: 92%
“…However, most of the studies were conducted outside of the U.S 5678,. except one small study4. Also, evidence on other American dietary patterns is very limited.…”
mentioning
confidence: 97%
“…12 All other studies of dietary patterns and lung cancer risk used data-driven methods. When principal components analysis was used to identify a 'prudent' or healthy diet pattern (characterized by high intake of fruits, vegetables, lean meats, whole grains and antioxidants), a reduced risk of lung cancer was observed for heavy smokers in an Italian cohort, 13 men in the Netherlands Cohort Study, 18 a US case-control study of never smokers 14 and several case-control analyses from Uruguay. 15,17 A 'high-meat' or 'Western' dietary pattern characterized by high intake of red and processed meat was associated with increased lung cancer risk in case-control studies from Uruguay 15-17 and a Netherlands cohort, 18 but was not associated with lung cancer risk in an Italian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…10 Examining dietary patterns considers that individual dietary components can be highly correlated or have synergistic or antagonistic biologic interactions that produce associations with disease risk that cannot be captured by studying a single food or nutrient. 11 In previous studies of dietary patterns and lung cancer risk, [12][13][14][15][16][17][18][19] all but one study 12 used data-driven approaches, such as factor analysis, which create dietary groupings that are unique to each study and do not allow for comparison across studies. An alternative approach is to use indices to define patterns a priori, based on dietary guidelines or recommendations, which can be used to compare diet quality across study populations.…”
Section: Introductionmentioning
confidence: 99%
“…For lung cancer risk, it may also be important to assess the interaction of diet with smoking patterns. In fact, one study showed that a "healthy eating" pattern that included vegetables, fruits, and low-fat foods was associated with a significant reduction in lung cancer risk among those who never smoked (33). Assessment of diet quality in the NIH-AARP Diet and Health study (N = 460,770) by scoring compliance with any of four common indices (Healthy Eating Index-2010, Alternative Healthy Eating Index-2010, alternative Mediterranean Diet score, and DASH Diet) yielded very similar results (34).…”
Section: Dietary Patterns and Lung Cancer Riskmentioning
confidence: 99%